Management of Sandhivata with special reference to Osteoarthritis - Manikanth M H,; Chaitrika P Hosur,; Ankita A Patil, (International Journal of Ayurveda and Pharma Research, 2024)
Sandhivata is Vataja nanatmaja Vyadhi and one of the common types of Vatavyadhi. It is most commonly witnessed in elderly patient more than 50 years due to Dhatukshaya. Females are more prone to Sandhivata due to hormonal imbalance after menopause. Since it is located in Marma sthana it is Kashtasadya. In this case study Upanaha with Goduma churana, Rasna churna, Kottumchukkadu churna, and Janu Basti with Ksheerabala taila, and Vyadhishardoola guggulu is used as Shamanayoga to manage Sandhivata. As a result observed that subject had significant relief in all cardinal symptoms. In this case study Godumadi Churna is used for Upanaha, Ksheerabala Taila used for Janu basti and Vyadhishardoola Guggulu is used as Shamanayoga for the management of Janusandhigata Vata. It is observed that all the symptoms are reduced and patient feels significant relief. This study can be taken for the further study in large sample size with different variety of patient to look over the results.